Monitoring and Analysis of Environmental Gamma Dose Rate around Serpong Nuclear Complex - I.P. Susila; A. Yuniarto; C. Cahyana (Atom Indonesia, 2017)
An environmental radiation monitoring system that continuously measures gamma dose rate around nuclear facilities is an important tool to present dose rate information to the public or authorities for radiological protection during both normal operation and radiological accidents. We have developed such a system that consists of six GM-based device for monitoring the environmental dose rate around Serpong Nuclear Complex. It has operated since 2010. In this study, a description of the system and analysis of measured data are presented. Analysis of the data for the last five years shows that the average dose rate levels were between 84-99 nSv/h which are still lower than terrestrial gamma radiation levels at several other locations in Indonesia. Time series analysis of the monitoring data demonstrates a good agreement between an increase in environmental gamma dose rate and the presence of iodine and argon in the air by in situ measurement. This result indicates that system is also effective for an early warning system in the case of radiological emergency.